Electrical engineer's reference book - Laughton, M. A.; Warne, D. F. (Oxford [England] ; Burlington, MA : Newnes, 2003)
For ease of use, this edition has been divided into the following subject sections: general principles; materials and processes; control, power electronics and drives; environment; power generation; transmission and distribution; power systems; sectors of electricity use. New chapters and major revisions include: industrial instrumentation; digital control systems; programmable controllers; electronic power conversion; environmental control; hazardous area technology; electromagnetic compatibility; alternative energy sources; alternating current generators; electromagnetic transients; power system planning; reactive power plant and FACTS controllers; electricity economics and trading; power quality. *An essential source of techniques, data and principles for all practising electrical engineers *Written by an international team of experts from engineering companies and universities *Includes a major new section on control systems, PLCs and microprocessors.
Units, mathematics and physical quantities -- Electrotechnology -- Network analysis -- Fundamental properties of materials -- Conductors and superconductors -- Semiconductors, thick and thin-film microcircuits -- Insulation -- Magnetic materials -- Electroheat and materials processing -- Welding and soldering -- Electric measurement -- Industrial instrumentation -- Control systems -- Digital control systems -- Microprocessors -- Programmable controllers -- Power semiconductor devices -- Electronic power conversion -- Electrical machine drives -- Motors and actuators -- Lighting -- Environmental control -- Electromagnetic compatibility -- Health and safety -- Hazardous are technology -- Prime movers -- Alternative energy sources -- Alternating current generators -- Batteries -- Overhead lines -- Cables -- HVDC -- Power transformers -- Switchgear -- Protection -- Electromagnetic transients -- Optical fibres in power systems -- Installation -- Power system planning -- Power system operation and control -- Reactive power plant and FACTS controllers -- Electricity economics and trading -- Power quality -- Road transport -- Railways -- Ships -- Aircraft -- Mining applications -- Standards and certification.
Previous ed.: edited by G.R. Jones, M.A. Laughton, M.G. Say. Oxford : Butterworth-Heinemann, 1993.
Includes bibliographical references and index.
Keywords: Electrical engineering; Electronic books